2011
DOI: 10.1172/jci44929
|View full text |Cite
|
Sign up to set email alerts
|

MEK-ERK pathway modulation ameliorates disease phenotypes in a mouse model of Noonan syndrome associated with the Raf1L613V mutation

Abstract: Hypertrophic cardiomyopathy (HCM) is a leading cause of sudden death in children and young adults. Abnormalities in several signaling pathways are implicated in the pathogenesis of HCM, but the role of the RAS-RAF-MEK-ERK MAPK pathway has been controversial. Noonan syndrome (NS) is one of several autosomal-dominant conditions known as RASopathies, which are caused by mutations in different components of this pathway. Germline mutations in RAF1 (which encodes the serine-threonine kinase RAF1) account for approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
190
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(204 citation statements)
references
References 81 publications
11
190
0
3
Order By: Relevance
“…In agreement with this, earlier reports incidentally showed that Mek inhibitors can rescue growth defect in other NS mouse models (RAF1 L613V/+ and SOS1 E846K/E846K ) [7,66]. Altogether, these reports suggest that pharmacological regulation of Ras/MAPK could be an alternative approach to treat short stature in NS patients, even though a lot requires to be accomplished to assess the efficacy and safety of these Figure 1.…”
Section: Role Of Ptpn11/shp2 Mutant Causing Ns In Ras/mapk Upregulatisupporting
confidence: 67%
“…In agreement with this, earlier reports incidentally showed that Mek inhibitors can rescue growth defect in other NS mouse models (RAF1 L613V/+ and SOS1 E846K/E846K ) [7,66]. Altogether, these reports suggest that pharmacological regulation of Ras/MAPK could be an alternative approach to treat short stature in NS patients, even though a lot requires to be accomplished to assess the efficacy and safety of these Figure 1.…”
Section: Role Of Ptpn11/shp2 Mutant Causing Ns In Ras/mapk Upregulatisupporting
confidence: 67%
“…For example, mice that carry a Sos1 mutation develop multiple NS features, and these defects can be prevented or their expression reduced by MEK inhibitor treatment during the early stages of life (47). Postnatal MEK inhibitor treatment also reverses some NS symptoms in Raf1 mutant mice (48), and rapamycin normalizes HCM in LS mouse models (5). Analogous models for the new NS genes defined here and by others (28) could prove important for personalizing RASopathy therapy.…”
Section: Significancementioning
confidence: 63%
“…The identification of a Thr188-phosphorylation site on ERK2 might be a first step in this direction: this phosphorylation can selectively activate hypertrophic ERK1/2 functions and, therefore, may be targeted without dangerous side effects. Mutant mice that lack this phosphorylation site show preserved cardiac structure and function and attenuated hypertrophic response, indeed demonstrating that ERK1/2 can be selectively targeted, at least in the adult patient (59).…”
Section: Future Directions For Therapymentioning
confidence: 93%
“…RAF1 mutations have been more frequently found to be associated with HCM, and nearly all NS patients with RAF1 mutations exhibit HCM (58). Like NS patients, mice heterozygous for the NS-associated RAF1 mutation exhibit eccentric cardiac hypertrophy (59). A mouse model of a constitutively active form of BRAF has also been created (60).…”
Section: Pathophysiological Signaling: Experimental Relevance Of the mentioning
confidence: 99%
See 1 more Smart Citation